Malaysian local functional food attributes and customer satisfaction / Fadzilah Mohd Shariff, Dg. Khairunisa Ahmad Sapawi and Hassnah Wee - Mohd Shariff, Fadzilah; Ahmad Sapawi, Dg. Khairunisa; Wee, Hassnah (2016)
The purpose of this article is to identify the local functional food attributes and literature on their relationship with customer satisfaction. Quality functional food attributes can provide a powerful competitive advantage towards consumer behavior. The literature indicated that the impact of local functional food taste, appearance and functionality are influenced with customer satisfaction. The study proposes six propositions, focusing on the local functional food attributes which correspond with customer satisfaction. It is believed that this article will provide clear insights into how local functional food attributes affect satisfaction. The assessment is vital as customer satisfaction is the key ingredient in capturing customer loyalty and the retention of purchase.